2017
DOI: 10.1111/jre.12486
|View full text |Cite
|
Sign up to set email alerts
|

Gingival tissue, an extrasynovial source of malondialdehyde‐acetaldehyde adducts, citrullinated and carbamylated proteins

Abstract: Background and Objective Postranslational modification of proteins can lead to the production of autoantibodies and loss of immune tolerance. This process has been hypothesised to be a critical factor in the pathogenesis of rheumatoid arthritis. The objective of this study was to demonstrate that inflamed human gingival tissue provides an extrasynovial source of malondialdehyde‐acetaldehyde adducts, citrullinated and carbamylated proteins all of which are considered to be linked to the development of rheumatoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Interestingly, the results of the current study also indicated that the patients with only periodontitis had significantly higher circulating levels of CarP than the controls, which is supported by the findings of another study that showed the presence of CarP in inflamed periodontal tissue [ 17 ]. However, the serum NETs levels were comparable between the patients with periodontitis and controls in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the results of the current study also indicated that the patients with only periodontitis had significantly higher circulating levels of CarP than the controls, which is supported by the findings of another study that showed the presence of CarP in inflamed periodontal tissue [ 17 ]. However, the serum NETs levels were comparable between the patients with periodontitis and controls in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Experimental arthritis studies have also shown that the appearance of anti-CarP antibodies in the sera precedes the onset of RA [ 15 , 16 ]. Recently, the presence of CarP was also demonstrated in inflamed periodontal tissue from patients with mild to moderate periodontitis [ 17 ]. These findings led to the hypothesis that protein carbamylation in patients with RA may also be shared by periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…However, while our data support the notion that this autocitrullinome does not act as a trigger of initial ACPA production as occurs during early stages of RA, we cannot rule out that autocitrullinated P. gingivalis proteins may contribute to autoimmune responses during later stages of disease (Kudo-Tanaka et al 2007). Moreover, host-derived inflammatory cues, as may arise during periodontitis that is driven by P. gingivalis or other oral pathobionts but also nonmicrobial factors (Curtis et al 2011), may induce posttranslational protein modifications, including citrullination and carbamylation (Bright et al 2018), and thus could be a mechanism linking periodontitis and RA.…”
Section: Discussionmentioning
confidence: 99%
“…OxLDL plays a key role in the inflammation of arterial wall and atherogenesis. Oxidized LDLs are also present in saliva fluid (De Giuseppe et al 2015), and recently, Bright et al (2018) reported that malondialdehyde acetaldehyde (MAA) adducts are increased in gingivitis and periodontitis lesions.…”
Section: Introductionmentioning
confidence: 99%